2019
DOI: 10.1186/s12976-019-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of group A streptococcal carrier on the epidemic model of acute rheumatic fever

Abstract: Background Group A streptococcus (GAS) is the most frequent cause of bacterial pharyngitis in school-aged children. The postinfection sequel as acute rheumatic fever (ARF) and rheumatic heart disease that cause morbidity and mortality among young people is public health concerns in several developing countries. Asymptomatic carriage state of GAS is not fully understood in terms of host and bacterial factors. Although the ability of transmitting GAS of the asymptomatic carriers is relatively low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…RHD can lead to complications such as heart failure, endocarditis, embolic stroke, and atrial fibrillation, which may be fatal in severe cases ( 9 ). RHD is the leading cause of morbidity and mortality in children aged 5–15 years ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RHD can lead to complications such as heart failure, endocarditis, embolic stroke, and atrial fibrillation, which may be fatal in severe cases ( 9 ). RHD is the leading cause of morbidity and mortality in children aged 5–15 years ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Acute pharyngitis is an acute, specific or non-specific inflammatory response of the pharyngeal mucosa, submucosa and lymphatic tissues and is a common disease that occurs in children between the ages of 5 and 15 years ( 1 , 9 ). The main clinical manifestations are sore throat, painful swallowing and fever.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is recent evidence that other routes may play an important role in the transmission: oronasal secretions, small airborne particles, skin-to-skin contact, surfaces, bedding and fabrics, food, and insects [ 6 , 7 ]. Though spread is from infectious individuals, some studies suggest that transmission from carriers may be of epidemiological importance [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…dust (airborne) [20][21][22][23][24], skin-to-skin contact (direct contact) [19,[25][26][27], surfaces (indirect contact) [28][29][30], bedding and fabrics (indirect contact) [31][32][33], food (vehicle) [34,35], and insects (biological vectors) [36][37][38]. Both the infectious and carrier state may lead to transmission, dominated by the infectious state [39,40]. A few studies have reported Strep A transmission from carriers to uninfected individuals who have subsequently become symptomatic [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%